Faktor-Faktor yang Mempengaruhi Ekspor Indonesia, 2000.I-2008.I - Nunik Rifa'atul Mahmudah; Irma Suryahani (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2010)
The aim of this research are to enquiry the influence of exchange rate rupiah to USD, Gross Domestic Product (GDP), and world oil price toward export of Indonesia during 2000.I-2008.I. The research methods are descriptive and quantitative analyses using secondary data. The analysis tool is path analysis to show direct and indirect influences of Indonesia’s export. This research also uses t-test to show partial influence and F-test to know together influence. Between those three variables, world oil price is the most influence variable of Indonesia's export. Keywords: exchange rate, export, gross domestic product, world oil price